Recent Advances of Aesthetic Gynaecology: A Narrative Review - Dhruva Piyush Halani; Arpita Jaiswal (Journal of Clinical and Diagnostic Research, 2023)
In the vast field of gynaecology, Female Cosmetic Genital Surgery (FCGS) is the newest and fastest growing sub specialty due to sexual distress and vaginal laxity. It includes operations intended to alter the genitalia of women in terms of function and/or aesthetics. Using electronic databases including MEDLINE/PubMed, Embase, and Scopus, a literature review search with current advancements was carried out without regard to dates or research designs. The search was based on 40 different cosmetic gynaecological terms, including “surgical vaginoplasty,” “labiaplasty,” “vaginal rejuvenation,” “vaginismus,” and “energy based devices,” amongst others. All english full-text prospective, retrospective, and interventional studies describing cosmetic gynaecological procedures that included at least five participants were considered. Efficacy and satisfaction metrics were highly variable ranging from validated questionnaires to no outcome subjectively or objectively quantified. This review provides an overview of the developing field of cosmetic gynaecology as well as the opinions of the authors and current developments in the study of this therapeutic area. Vaginal laxity is common and may impact sexual function and quality of life. Expanding aesthetic gynaecology may benefit the patients in their Female Sexual Function Inventory (FSFI) scores, intimate wellness, and psychosocial function.